The Rising Racism in Europe: Example Of Pegida - M. Nail; Alkan (Gazi Akademik Bakış)
The racist approaches has began to take place on international area intensively after Cold-War period in the European Union countries. Generally, when we think about xenophobia and racism in Europe, Germany becomes the first country that comes to mind. However, the European Parliament Election in 2014 has shown that the racist approaches are not restricted to Germany. Xenophobia and racism are increasing day by day in nearly all the European Union countries. So far, the racism has been raised as a form of Islamophobia in expressions of far-right parties in Europe. Today the movement, which arised in September 2014 and called Pegida, has started to use these approaches. In this article the Pegida movement will be examined in the context of rising Islamophobia, racism and xenophobia in the European countries recently.